PENDAMPINGAN SADAR STUNTING DESA LAPPA ANGING KOTA PAREPARE - Ismirawati, Nur; Zakiyah, Nur; M K, Pratiwi (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
The prevalence of stunting in the city of Parepare continues to fluctuate. Watang Bacukiki Village, located in Lappa Anging Village, is a remote area outside the city limits with limited access to education. It is also a region with a high incidence of stunting. One strategy for controlling the stunting rate is to educate the community about the causes and consequences of stunting. This approach can help to reduce the prevalence of stunting by empowering communities to take action to improve their understanding of this issue and its associated risks. The community service activity was conducted using a combination of lecture, discussion, and question-and-answer methods. Prior to the activity, a pretest was administered to 22 respondents, all of whom were female and ranged in age from 27 to 45 years. This provision aims to ascertain the respondents' initial knowledge about stunting and then provide them with education and subsequent measurement of changes in their knowledge. A data analysis was conducted to ascertain these changes, employing the McNemar test. The results demonstrated a statistically significant change with a p-value of 0.000, exceeding the alpha level of 0.05. This indicates that there were notable shifts in knowledge before and after the educational intervention. The findings suggest that there were changes in the knowledge of the Lappa Anging Village community regarding stunting. Based on these results, it is recommended to re-evaluate the service activities, for instance, by innovating high-nutrition food recipes for pregnant women and children under two years of age.